Analysis of Islamic Religious Education Learning Management for Children with Special Needs at SLBN Autis North Sumatera - Maulida, Sri Aqilah; Neliwati, Neliwati (Jurnal Paedagogy, 2025)
This study aims to analyze the management of Islamic Religious Education (PAI) learning for Children with Special Needs (ABK) at SLBN Autis North Sumatera, focusing on three main aspects, namely planning, implementation, and learning assessment. This research uses a qualitative approach with phenomenological methods. Data collection techniques were conducted through in-depth interviews, direct observation, and documentation studies, with informants consisting of Islamic Religious Education teachers, principals, and their deputies. All data obtained were analyzed using the analysis model of Miles and Huberman, which consists of three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that learning planning begins with an initial assessment to understand the characteristics of students, but the teaching modules prepared by Islamic Education teachers are still general and not fully individualized. Learning implementation is conducted twice a week, every Tuesday and Thursday, with a flexible and differentiative approach. Teachers use individual and small group strategies, as well as varied learning media such as pictures, videos, and Islamic songs. Teaching and learning activities are also supported by regular principal supervision. Learning assessment is carried out adaptively through written, oral, practical methods, attitude observation, and student involvement in religious activities. However, teachers still face challenges in assessing.